Sea of glory : America's voyage of discovery : the U.S. Exploring Expedition, 1838-1842 - Philbrick, Nathaniel (New York, N.Y. : Viking, 2003)
America's first frontier was not the West; it was the sea- and no one writes more eloquently about that watery wilderness than Nathaniel Philbrick. In his bestselling In the Heart of the Sea Philbrick probed the nightmarish dangers of the vast Pacific. Now, in an epic sea adventure, he writes about one of the most ambitious voyages of discovery the Western world has ever seen-the U.S. Exploring Expedition of 1838- 1842.
Includes information on Maine naval officer James Alden, and the Georges Bank survey.
Includes bibliographical references (p. 415-436) and index.
Accelerated Reader AR
Keywords: Alden, James, -- 1810-1877.; Wilkes, Charles, -- 1798-1877.; Ethnological expeditions -- History -- 19th century; Ethnology -- United States -- History -- 19th century; Ethnology -- Oceania -- History -- 19th century; Georges Bank